PENGARUH PEMBERIAN LATIHAN SENAM AEROBIC HIGH IMPACT UNTUK MENINGKATKAN DAYA TAHAN KARDIORESPIRASI PADA SKIPPER ARUNG JERAM - I Putu Darmawijaya; Made Gede Dwi Suputra; Agung Wahyu Permadi (Sport and Fitness Journal, 2019)
ABSTRACTPhysical fitness is a key requirement for a skipper in the river, with the ability of cardiac endurance (cardiorespiration) as a basis for the endurance of muscle work for a long time. One exercise that can improve cardiorespiratory endurance is high impact aerobic exercise. The experimental method was applied through high impact aerobic exercise exercise with One Group Pretest-posttest Design and performed at My Adventure Rafting with a sample size of 21 people for 3 times a week in 4 weeks of research. Based on paired t test, it is found that aerobic high impact gymnastics have an effect on the improvement of cardiorespiratory endurance. Where the probability value (p) is significant is 0,000 which means 0.000 <0.05 then there is a significant difference.Keywords: Skipper, Cardiorespiratory Endurance, Aerobic High Impact Gymnastic